(untitled) (Annals of Medical Research, 2024)
Aim: Leishmaniasis is a disease complex caused by Leishmania protozoan microorganisms, transmitted through the bite of the vector female sandfly. Cutaneous leishmaniasis (CL) is the most common clinical type. The formation, clinical features, and healing process of CL are determined by the characteristics of the host and the parasite. Our study aims to examine the clinical and sociodemographic characteristics of patients diagnosed with CL at our clinic of dermatology and venereal diseases. Materials and Methods: In this prospective study, the clinical and demographic characteristics such as age, gender, number of lesions, size of lesions, duration of lesions, localization of lesions, and treatments received for CL diagnosis were examined in 74 patients diagnosed with CL by microscopic examination at Şanlıurfa Training and Research Hospital’s dermatology and venereal diseases clinic between October 2022 and March 2023. Results: In our study, 40 (54%) patients were male, and 34 (46%) were female. The average age of the patients was 16.4±9.31 years. The number of lesions varied between 1 and 9, with a total of 158 lesions. Lesions were most frequently (64%) located on the face. The average duration of lesions was 4.9±3.8 months, and the average size was 4.6±3.7 cm. 7 patients had a family history of CL. The diagnosis of CL in all patients was made by cutaneous smear. Post-diagnosis, 14 patients (19%) received systemic meglumine antimonate treatment, and 60 (81%) received intralesional meglumine antimonate treatment. Conclusion: The data from our study demonstrate similar clinical and sociodemographic characteristics to those found in other studies conducted in our country.